Characterization of murine macrophages from bone marrow, spleen and peritoneum - Wang, Changqi; Yu, Xiao; Cao, Qi; Wang, Ya; Zheng, Guoping; Tan, Thian Kui; Zhao, Hong; Zhao, Ye; Wang, Yiping; Harris, David CH (BMC immunology, 2013)
Macrophages have heterogeneous phenotypes and complex functions within both innate and adaptive immune responses. To date, most experimental studies have been performed on macrophages derived from bone marrow, spleen and peritoneum. However, differences among macrophages from these particular sources remain unclear. In this study, the features of murine macrophages from bone marrow, spleen and peritoneum were compared. We found that peritoneal macrophages (PMs) appear to be more mature than bone marrow derived macrophages (BMs) and splenic macrophages (SPMs) based on their morphology and surface molecular characteristics. BMs showed the strongest capacity for both proliferation and phagocytosis among the three populations of macrophage. Under resting conditions, SPMs maintained high levels of pro-inflammatory cytokines expression (IL-6, IL-12 and TNF-α), whereas BMs produced high levels of suppressive cytokines (IL-10 and TGF-β). However, SPMs activated with LPS not only maintained higher levels of (IL-6, IL-12 and TNF-α) than BMs or PMs, but also maintained higher levels of IL-10 and TGF-β. Our results show that BMs, SPMs and PMs are distinct populations with different biological functions, providing clues to guide their further experimental or therapeutic use.